Seksualitas SEKSUALITAS PADA AWAL MENOPAUSE BURUH GENDONG DIPASAR BERINGHARJO YOGYAKARTA: SEKSUALITAS PADA AWAL MENOPAUSE - Brilian Dini MA. Iballa; Eugenius Phyowai Ganap; Yekti Satriyandari (Jurnal Ilmu Kebidanan, 2023)
Menopause is a physiological sequence of the female body related to its reproductive function, which is marked by a decrease in the production of female sex hormones, namely estrogen and progesterone. The method used in this research is correlative (correlative research) with a cross sectional study approach and data analysis using Chi-Square. The results in this study where the results of the analysis show that there is a significant relationship between the early phase of menopause and problems with sexual activity. Suggestion: it is hoped that this can serve as input for health professionals, especially midwives, to become reproductive health counselors for postmenopausal women, especially menopausal women who are busy (work).